THE COMMUNICATIVE GRAMMAR TRANSLATION METHOD: A PRACTICAL METHOD TO TEACH COMMUNICATION SKILLS OF ENGLISH - Andi Kaharuddin (Universitas Islam Negeri Alauddin Makassar, 2018)
This paper is theoretically aimed at discussing how to teach communication skills (written and spoken) through a combination between the classic grammar translation and the modern communicative language teaching). The combination not only results in the formation of a new method which is here known as the communicative grammar translation method, but also in the formation of a new methodology in English language pedagogy which might be applied by English teachers to teach communication skills in the classrooms. The methodology of this new method consists of three special procedures i.e. The first is structural procedure which allows the learners to learn grammar rules and vocabulary. The second is transitional procedure which gives opportunity to the students to practice using the rules in translation and pronunciation drills. The third is communicative procedure which also gives the learners opportunity to use their knowledge of grammar and vocabulary in communicative activities. The implementation of the three procedures is believed able to achieve three learning outcomes i.e. making the learners able to deliver English basic communication both in spoken and written, promoting the learners’ language accuracy and fluency in communication, and improving the learner knowledge of grammar and vocabulary to enhance initiatives in communication.